Prevalencia del Dengue, Serotipos circulantes y Factores de Riesgo en América Latina: Revisión sistemática - Gallardo Aguilar, Emily Daniela (2025)
Dengue is a disease caused by a virus of the gender flavivirus, it is classified into four main serotypes: DENV-1, DENV-2, DENV-3, and DENV-4 with humans are the main host, and the Aedes aegypti mosquito is vector. Its incidence increases during warm and rainy seasons, becoming it in a seasonal disease. In 2023 the 80% of the global cases of dengue were noticed in America, while that still the week 42 of 2024 were reported more than 12 million cases. Therefore, this research has as objective to determine the prevalence of dengue during the years 2023-2024, identify the main circulating serotypes at a regional level according to their geographic distribution and clinical characteristics, and analyze the relationship between prevalence and risk factors associated with the disease. For this purpose, I have realized a systematic review with a total of 42 studies analytical cross-sectional type of prevalence and narrative textual evidence, selected through the PICO strategy and evaluated with the JBI method where the bias was low. I have included some scientific articles from databases such as PubMed, SciELO and Lilacs, also, some epidemiological bulletins. The results showed that Brazil had the highest prevalence rate of dengue in Latin America, attributed to climate change and lack of prevention, while Mexico and El Salvador managed to reduce it with effective action plans. The four serotypes of the disease circulate at a regional level, highlighting DENV-2 and DENV-3 associated with more severe clinical conditions. In addition, it was revealed that the economic level is the risk factor with the greatest influence on the increase in the prevalence of dengue, followed by the climate change reflected in the increase of the temperature